A contribuição da música na formação de Pedagogos(as) - Sammour, Gabriele Segecic (2025)
This undergraduate thesis investigates the impact of music on the Pedagogues´education, with the aim of promoting creative and meaningful educational practices. The main objective is to examine the role of music in the formation of Pedagogues and its implications for pedagogical practices. The specific objectives are: to analyze the theoretical bases that support this relationship; to investigate the formative experiences of Pedagogues in relation to music education; and to evaluate the results of the presence of music in daily pedagogical practices. The methodology was established through bibliographical research. The results point to the need for an in-depth understanding of the benefits of music education in the Pedagogues´ formation and its contributions to an education that values knowledge of Art, cultural diversity, collective practices, and the perception of oneself and other people. Music enriches the Pedagogues´education by developing cognitive, emotional and social aspects, in addition to strengthening the ability to create educational environments that promote the expansion of sensitivity, creativity and student engagement, preparing them for the cultural, artistic and pedagogical challenges present in different educational contexts.